Cobalt-induced cardiomyopathy – do circulating cobalt levels matter?. Issue 6 (1st June 2021) - Jenkinson, Mark R. J.; Meek, R. M. Dominic; Tate, Rothwell; MacMillan, Sandy; Grant, M. Helen; Currie, Susan
Abstract : Elevated levels of circulating cobalt ions have been linked with a wide range of systemic complications including neurological, endocrine, and cardiovascular symptoms. Case reports of patients with elevated blood cobalt ions have described significant cardiovascular complications including cardiomyopathy. However, correlation between the actual level of circulating cobalt and extent of cardiovascular injury has not previously been performed. This review examines evidence from the literature for a link between elevated blood cobalt levels secondary to metal-on-metal (MoM) hip arthroplasties and cardiomyopathy. Correlation between low, moderate, and high blood cobalt with cardiovascular complications has been considered. Elevated blood cobalt at levels over 250 µg/l have been shown to be a risk factor for developing systemic complications and published case reports document cardiomyopathy, cardiac transplantation, and death in patients with severely elevated blood cobalt ions. However, it is not clear that there is a hard cut-off value and cardiac dysfunction may occur at lower levels. Clinical and laboratory research has found conflicting evidence of cobalt-induced cardiomyopathy in patients with MoM hips. Further work needs to be done to clarify the link between severely elevated blood cobalt ions and cardiomyopathy. Cite this article: Bone Joint Res  2021;10(6):340–347.